Penerapan Teknik Pemupukan pada Aklimatisasi Anggrek Hasil Persilangan Vanda di Kecamatan Matesih Kabupaten Karanganyar - Sri Hartati; Ahmad Yunus; Ongko Cahyono; Bayu Aji Setyawan (Universitas Sebelas Maret, 2019)
Title: Application of Fertilization Techniques in the Orchid Acclimatization of Vanda Crosses in Matesih District, Karanganyar Regency. The development of orchid agribusiness requires the mastery of adequate cultivation technology, including tissue culture technology. One area that develops orchids in the center of ornamental plants Karanganyar Regency is Plosorejo Village, Matesih District. The Community Partnership Program (PKM) involves two local orchid farmer groups aimed at disseminating the results of research conducted by the community service team, which were in the form of the application of techniques for using leaf fertilizer. The method used in this activity was the acclimatization and treatment of leaf fertilization. This program can improve the knowledge and skills of participants in caring for orchids from crossing and supporting the development of orchids nationally. The enthusiasm of the participants in participating in the activity was very high with an average attendance of more than 70% in each activity. The evaluation results showed that more than 80% of the orchid seedlings acclimated by the participants managed to grow well. The development of seedling growth (seedling height, leaf length and number of leaves) also worked well.